Real-Time PCR based test for the early diagnosis of Haplosporidium pinnae affecting fan mussel Pinna nobilis. - Monserrat López-Sanmartín; Gaetano Catanese; Amalia Grau; José María Valencia; Jose Rafa García-March; José Ignacio Navas (PLoS ONE, 2019)
Noble pen shell or fan mussel, Pinna nobilis Linnaeus (1758), protected since 1992, was incorporated into the Spanish Catalogue of Threatened Species (Category: Vulnerable, Royal Decree 139/2011). The status is presently in the process of being catalogued as critically endangered, pending approval by Spanish Government (https://www.mapama.gob.es/es/biodiversidad/participacion-publica/Borrador_OM_situacion_critica.aspx). The International Union for the Conservation of Nature (IUCN) alerted the countries of the Mediterranean basin to the "emergent situation" due to serious mortality events suffered by the fan mussel, putting it in serious risk of extinction. Thus, emergency actions have been implemented by Spanish authorities in which several research institutes from all over the country are involved. The parasite, Haplosporidium pinnae, was recently characterized by histology, TEM, SEM and molecular biology techniques and it was considered responsible for the mass mortality of P. nobilis in the Mediterranean Sea. In this context, the aim of this study has been to develop species-specific quantitative PCR (qPCR) protocol carrying out a fast, specific and effective molecular diagnose of H. pinnae. In this sense, the detection limit for qPCR was equal to 30 copies of SSU rDNA / ng of DNA using plasmid alone and when 100ng DNA of non-infected oyster were added. The qPCR assay revealed that 94% of the 32 analysed mantle tissues of fan mussel were infected by H. pinnae, showing a high sensitivity and specificity for its detection (100% if we don't consider negative and too much degraded samples). This technique will allow us to make quicker follow-ups of the disease, allowing us to get a better understanding of its evolution in order to help in the rescue of P. nobilis populations.